ANALYSIS CONCENTRATION OF NITRATE, PHOSPHATE, SILICATE AND RELATIONSHIP WITH DIATOM ABUDANCE IN WATERS TANJUNG TIRAM DISTRCTS BATU BARA REGENCY OF NORTH SUMATERA PROVINCE - Hidayat, Rahmat; Nedi, Syahril; Nurrachmi, Irvina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2019)
Input of nutrients into the waters from various human activities (residential, agriculture and industry) has the potential to cause changes in the physical, chemical and biological conditions of the waters. The study aims to determine the relationship of concentrations of nitrate, phosphate and silicate with the abundance of diatoms in the Tanjung Tiram waters. The method used is the survey method, the determination of the location of sampling is done by purposive sampling, data analysis (multiple regression). Based in the results of laboratory analysis nitrate concentrations ranged from 0,0819 – 0,1167 mg/l, the phosphate concentration ranged from 0,1002 – 0,1526 mg/l, and silicate concentration ranged from 0,04447 – 0,5418 mg/l. The abundance of diatoms in Tanjung Tiram waters ranged from 156,9 – 302,8 ind/l. The results of statistical analysis of the relationship of nitrate, phosphate and silicate with the abundance of diatoms are expressed in terms of equation Y = 350,906 – 58,065Nitrate– 2644,624phosphate+ 440,363Silicate. This statement explains the concentration of nitrate, phosphate related negative (-) to the abundance of diatoms and silicate positive (+) related to the abundance of diatom. This condition shows that the nutrient concentration in these waters is relatively high so that it affects the abundance of diatoms.